2010
DOI: 10.1007/s11240-010-9874-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro haploid and dihaploid production via unfertilized ovule culture

Abstract: Haploids and doubled haploids are very important in plant breeding, enabling the time needed to produce homozygous lines to be shortened compared with conventional breeding. In the present review, emphasis is given to haploid induction through unfertilized ovule/ovary culture. Attention is given to induction of haploid plants from female gametophyte culture through analysis of factors in the processes of gynogenesis, including genotype selection, stage of ovule development, pretreatment, and culture media cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 59 publications
(49 reference statements)
6
82
0
4
Order By: Relevance
“…The benefits of various starvation and stress techniques have been reported in several plant species (Gu et al 2004;Zoriniants et al 2005;Dunwell 2010;Zhuang et al 2010;Bhowmik et al 2011;Chen et al 2011;Seguí-Simarro et al 2011;Takahira et al 2011;Winarto and Teixeira da Silva 2011). A 28-day treatment of spikes at 4°C was shown to lead to a much increased yield of microspore calli in cereals (Dunwell 2010).…”
Section: Cold and Heat Pretreatmentsmentioning
confidence: 99%
“…The benefits of various starvation and stress techniques have been reported in several plant species (Gu et al 2004;Zoriniants et al 2005;Dunwell 2010;Zhuang et al 2010;Bhowmik et al 2011;Chen et al 2011;Seguí-Simarro et al 2011;Takahira et al 2011;Winarto and Teixeira da Silva 2011). A 28-day treatment of spikes at 4°C was shown to lead to a much increased yield of microspore calli in cereals (Dunwell 2010).…”
Section: Cold and Heat Pretreatmentsmentioning
confidence: 99%
“…Alternatively, true homozygous lines can be efficiently and rapidly obtained by in vitro culture of gametophytic cells, followed by spontaneous or induced chromosome doubling. These homozygous doubled haploids have been induced via either androgenesis (pollen or anther culture) or gynogenesis (ovule or ovary culture) processes, or induced by pollination with irradiated pollen (Islam, 2010;Chen et al, 2011;Lazaridou et al, 2011;Gałązka and Niemirowicz-Szczytt, 2013). In several plants, including sugar beet and gentians, in vitro culture of unpollinated ovules or ovaries have been reported to be more efficient in haploid and doubled haploid production than pollen or anther culture (Gürel et al, 2000;Chen et al, 2011;Doi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, calcium ions helped harden the ovary tissue which made it easy to get thinner slices from which the ovules could contact to the medium directly. Moreover, the culture medium composition was critical for the induction of embryogenesis and could be separated by formula into induction and regeneration media (Chen et al, 2010). Gynogenesis consists of two stages, firstly, the induction stage, in this stage ovaries required a low level of growth regulators and were kept in the dark; and secondly, the regeneration stage, in this stage ovules were transferred to a medium with a high concentration of growth regulators and kept under light.…”
Section: Discussionmentioning
confidence: 99%
“…Some clones required a medium with a high hormone concentration (BAP: IAA at a ratio of 5:1) for regeneration, while some accessions were regenerated using the same low hormone level (BAP: IAA at a ratio of 2:1) used for the induction stage. Chen et al (2010) also reported that the donor genotype was one of many factors important for unfertilized ovary/ovule culture; Science Publications AJABS gynogenesis efficiency in plants was highly dependent on the variety used. Moreover, the quality of donor material and the growth condition of plants affected ovule gynogenesis.…”
Section: Discussionmentioning
confidence: 99%